2001
DOI: 10.1159/000056359
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Antiparakeratotic Potency of Calcitriol and Tacalcitol in Liposomal Preparations in the Mouse Tail Test

Abstract: In order to test the advantage of vitamin D3 preparations in liposomal form, calcitriol, the natural activated form of vitamin D3, and tacalcitol, a vitamin D3 analogue, were employed in various concentrations and using different vehicles in the mouse tail test, an animal model for testing the antiparakeratotic efficacy of topical medications. The optimal concentration in petrolatum turned out to be similar to that in commercial preparations. The liposomal preparations were sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Liposomes [60,61] Liposomes [62] Liposomes [63,64] challenge. The intricacies of the topical delivery into the psoriatic skin have lately been proposed to be addressed by the lipoidal carrier systems, such as liposomes.…”
Section: Musculoskeletal Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Liposomes [60,61] Liposomes [62] Liposomes [63,64] challenge. The intricacies of the topical delivery into the psoriatic skin have lately been proposed to be addressed by the lipoidal carrier systems, such as liposomes.…”
Section: Musculoskeletal Painmentioning
confidence: 99%
“…Several attempts have been made to incorporate the drug in various colloidal carriers. For instance, the drug has been incorporated into liposomes, [14,59] niosomes, [60][61][62] SLNs, [63] and nanocapsules. [64] These studies have been carried out in various animal models and reported to perform quite well.…”
Section: Dithranolmentioning
confidence: 99%
“…Similar results were also observed with tacalcitol in liposomes. The authors suggested that by using a liposomal preparation, the vitamin D 3 concentration can be reduced as compared with that of currently available commercial preparations without sacrificing therapeutic effect and meanwhile reducing local side‐effects such as skin irritation and systemic side‐effects 56 . Dithranol generally used as short contact therapy is safe and efficacious in the treatment of plaque type psoriasis.…”
Section: Indications For Liposomes As Drug Carriers In Dermatologymentioning
confidence: 99%
“…The authors suggested that by using a liposomal preparation, the vitamin D 3 concentration can be reduced as compared with that of currently available commercial preparations without sacrificing therapeutic effect and meanwhile reducing local side-effects such as skin irritation and systemic side-effects. 56 Dithranol generally used as short contact therapy is safe and efficacious in the treatment of plaque type psoriasis. However, its use is inconvenient and troublesome because of its side-effects such as skin irritation, burning sensation, staining and necrotizing effect on normal as well as the diseased skin.…”
Section: Figurementioning
confidence: 99%
“…Conventional liposomes increased the skin delivery of vitamin D3 and dithranol in the treatment of psoriasis [42]. In the case of the plaque type psoriasis, the entrapment of dithranol in liposomes has promoted its epidermal bioavailability and enabled the dose lowering, resulting in the reduction of consequent dose-dependent side-effects [43].…”
Section: Conventional Liposomesmentioning
confidence: 99%